Hubungan Religiusitas dengan Kesehatan Mental pada Populasi Dewasa Muda Muslim di Indonesia - Bagas Rahmatullah; Cindy Febriani Thalia; Angga Adi Saputra; Adelia Nurul Aulia Basar; Andi Eka Septilla (Fakultas Psikologi Universitas Pancasila, 2023)
Religiosity is often associated with the good and bad condition of an individual's mental health so a lot of negative stigma arises on mental health issues. This study aims to scientifically prove the relationship between religiosity and mental health. This research method uses a quantitative method with an accidental sampling technique. To measure religiosity, the Muslim Religiosity Scale was used and to measure mental health, the Depression, Anxiety, Stress Scale 21 (DASS-21) was used. This study involved 133 participants from 13 provinces in Indonesia with 19.50% male participants and 80.50% female participants. Based on the results of the Paired Sample T-test, the results showed that there was no significant relationship between religiosity and the symptoms of mental health disorder, the correlation of religiosity and depression with r = -0.42; p > 0.05, with anxiety r = -0.29; p > 0.05, and with stress r = -0.36; p > 0.05. Based on the results of the study, we can interpret that the individual mental health aspect does not have a significant relationship with the high or low level of religiosity.